Physiological changes associated with copper sulfate-induced nausea and retching in felines - Murphey, Charles P.; Shulgach, Jonathan A.; Amin, Pooja R.; Douglas, Nerone K.; Bielanin, John P.; Sampson, Jacob T.; Horn, Charles C.; Yates, Bill J. (Frontiers in Physiology, 2023)
Nausea is a common disease symptom, yet there is no consensus regarding its physiological markers. In contrast, the process of vomiting is well documented as sequential muscular contractions of the diaphragm and abdominal muscles and esophageal shortening. Nausea, like other self-reported perceptions, is difficult to distinguish in preclinical models, but based on human experience emesis is usually preceded by nausea. Here we focused on measuring gastrointestinal and cardiorespiratory changes prior to emesis to provide additional insights into markers for nausea. Felines were instrumented to chronically record heart rate, respiration, and electromyographic (EMG) activity from the stomach and duodenum before and after intragastric delivery of saline or copper sulfate (CuSO4, from 83 to 322 mg). CuSO4 is a prototypical emetic test agent that triggers vomiting primarily by action on GI vagal afferent fibers when administered intragastrically. CuSO4 infusion elicited a significant increase in heart rate, decrease in respiratory rate, and a disruption of gastric and intestinal EMG activity several minutes prior to emesis. The change in EMG activity was most consistent in the duodenum. Administration of the same volume of saline did not induce these effects. Increasing the dose of CuSO4 did not alter the physiologic changes induced by the treatment. It is postulated that the intestinal EMG activity was related to the retrograde movement of chyme from the intestine to the stomach demonstrated to occur prior to emesis by other investigators. These findings suggest that monitoring of intestinal EMG activity, perhaps in combination with heart rate, may provide the best indicator of the onset of nausea following treatments and in disease conditions, including GI disease, associated with emesis.